SOCIO-ECONOMIC FACTORS OF ENTREPRENEURSHIP DEVELOPMENT IN RURAL COMMUNITIES - Rurak І. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article explores the system of socio-economic factors influencing business development in rural territorial communities of Ukraine. Entrepreneurship is viewed as a key mechanism for stimulating local development, increasing employment, strengthening the financial capacity of communities, and reducing socio-economic disparities between urban and rural areas. It is emphasized that under martial law, the importance of business activity for rural areas is growing, but so are the complexities of challenges associated with demographic decline, labor outflow, limited access to finance, and institutional instability. The study analyzes a complex set of interrelated factors shaping entrepreneurship in communities, namely demographic, economic, social, institutional, infrastructural, and security-related. It is substantiated that none of these groups of factors operate independently; rather, they form a multi-component environment in which the interaction among factors generates a synergistic effect. A generalized model of the systemic interaction of socio-economic factors is proposed, enabling the visualization of links between different impact blocks and identifying directions for enhancing the efficiency of business activity. Demographic risks associated with youth outmigration, population aging, and internal labor migration are analyzed, as they diminish both the labor and consumer potential of rural communities. The research examines barriers to accessing finance, including high interest rates, lack of credit history, and low financial literacy. The author highlights importance of developing microfinance mechanisms, digital financial services, and state-backed guarantees to stimulate local business initiatives. Special attention is given to the role of infrastructure and social capital as foundations for creating a favorable business environment. It is demonstrated that the institutional capacity of local self-government, the level of community trust, the availability of educational resources, and the presence of partnership networks are critically important prerequisites for unlocking entrepreneurial potential. In the wartime context, new forms of interaction between communities and international donors and partners are identified, which open additional channels of support for small and medium-sized enterprises. The study suggests a conceptual approach to strategic planning for entrepreneurship development in rural communities. The proposed model can serve as a practical tool for designing local business support programs that consider both internal resources and external challenges. The author concludes that business in rural communities is not an isolated phenomenon, but rather reflects the overall state of the socio-economic system, requiring a comprehensive policy aimed at long-term resilience, regional balance, and adaptability to crisis conditions.